The search for alternative temperate perennial pasture species for low to medium rainfall environments in Tasmania - Hall, E.J.; Reid, R.; Clark, B.; Dent, R. (NZGA: Research and Practice Series, 2016)
In response to the need to find better adapted and more persistent perennial pasture plants for the dryland pastures in the cool-temperate low to medium rainfall (500-700 mm) regions, over 1000 accessions representing 24 species of perennial legumes and 64 species of perennial grasses, were introduced, characterised and evaluated for production and persistence under sheep grazing at sites throughout Tasmania. The work has identified four alternative legume species in Talish Clover (Trifolium tumens). Caucasian Clover (T. ambiguum), Stoloniferous Red Clover (T. pratense var. stoloniferum), Lucerne x Yellow Lucerne Hybrid (Medicago sativa x M.sativa subsp. falcata); and two grass species in Coloured Brome (Bromus coloratus) and Hispanic Cocksfoot (Dactylis glomerata var hispanica). Keywords: persistence, perennial grass, perennial legume